Safeguarding and Protecting Children in the Early Years - Reid, James (Lecturer in childhood studies); Burton, Steven (London : Routledge, 2014)
This text provides a comprehensive guide to safeguarding and child protection in the early years. Aimed at students and practitioners, it offers an overview of recent developments in early years and safeguarding practice and sets out the legal and policy foundations for effective practice, highlighting areas of contemporary concern. Drawing on the everyday dilemnas and experiences of early years professionals, the book focuses on helping to seek solutions to both practical and moral issues in a context of legal duties and responsibilities.
"A David Fulton book."
Includes bibliographical references and index.
Keywords: Child welfare; Society